The evolution of BRAF-targeted therapies in melanoma: overcoming hurdles and unleashing novel strategies - Imani, Saber; Roozitalab, Ghazaal; Emadi, Mahdieh; Moradi, Atefeh; Behzadi, Payam; Jabbarzadeh Kaboli, Parham (Frontiers in Oncology, 2024)
Melanoma, a highly aggressive form of skin cancer, poses a significant global health burden, with 331,647 new cases and 58,645 deaths reported in 2022. The development of melanoma is influenced by various factors, including sunlight exposure and BRAFV600 mutations that activate the MAPK/ERK pathway. The introduction of BRAF and MEK inhibitors has revolutionized the treatment landscape for melanoma patients. However, innate and acquired therapeutic resistance remains a significant challenge. This review provides a comprehensive overview of the current state of BRAF-targeted therapies in melanoma, highlighting the efficacy and limitations of FDA-approved combinations of BRAF and MEK inhibitors such as vemurafenib, dabrafenib, trametinib, and cobimetinib. The review also explores the off-target effects of BRAF inhibitors on endothelial cells, emphasizing the need for more selective therapies to minimize vascular complications and metastatic potential. The article also discusses potential druggable targets, including ERK5, CD73, ALDH1A1, PLA1A, and DMKN, which are promising in addressing diagnostic hurdles and guiding personalized therapeutic decisions. Recent studies on regorafenib, ERK5 signaling, and CD73 inhibition are highlighted as novel strategies to overcome resistance and improve treatment outcomes. The review also delves into the role of advanced therapeutic tools, such as mRNA vaccines and CRISPR-Cas9, in revolutionizing personalized oncology by targeting specific genetic mutations and enhancing immune responses against melanoma. The ongoing synergy between advancing research, targeted interventions, strategic treatment combinations, and cost-effectiveness evaluations offers a promising pathway to elevate patient outcomes in the persistent battle against melanoma significantly.